PREVALENSI PREMENSTRUAL SYNDROME DAN PREMENSTRUAL DYSPHORIC DISORDER PADA WANITA DI LAPAS KLAS IIA KOTA YOGYAKARTA - , MUTIK SRI PITAJENG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Premenstrual syndrome (PMS) is a collection of physical and mental changes that started some days before menstruation and subside almost immediately at the time of menstruation is coming. Severe PMS is called Premenstrual dysphoric disorder (PMDD). Women inmates have more related factors of PMS/PMDD than general population. Objective: To find out the prevalence of PMS and PMDD in women inmates at Lapas Klas IIA Yogyakarta. Method: Quantitative research with descriptive survey approach. The subjects were women inmates. Questionnaire was used for data collection to get demographic information, menstrual history, and symptoms relevant to PMS and PMDD according to ACOG and DSM-IV criteria from Hapsari et al., (2004) which had been translated into Bahasa by Cahyanti et al., (2012). Data was collected 3 times from January-April 2014. Result: The prevalence of women inmates without PMS/PMDD were 13 (40,6%), women inmates with PMS were 13 (40,6%), women inmates with PMDD were 6 (18,8%). PMS and PMDD in women inmates disturbed activities of women inmates in prison such as disturbed developing program, social relationship, productivity, family relationship, and another activity. Most of women inmates with PMS felt breast tenderness (100,0%), anger (84,6%) and changed of appetite (76,9%). Most of women inmates with PMDD felt anxiety (100,0%), fatigue (100,0%), impaired concentration (100,0%), and breast tenderness (100,0%) as premenstrual symptoms. Conclusion: The prevalence of PMS and PMDD in women inmates were 40,6% and 18,8%. PMS and PMDD in women inmates was higher than general population in Indonesia.